PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS MAHASISWA MELALUI ACCELERATED LEARNING CYCLE - Fitriana Yolanda; Sindi Amelia (Jurnal Ilmiah Dikdaya, 2018)
This study examines the improvement of students' mathematical connection skills through the application of Accelerated Learning Cycle learning. Through quasi-experimental research with non-equivalent control groups, 100 students were included in the algebra and trigonometry courses in the FKIP UIR Mathematics Education Study Program. The research instrument used consisted of a mathematical connection test device. Data analysis using the Mann-Whitney test. The results of this study indicate that the increase in mathematical connection ability of experimental class students is better than the control class (p = 0,000, p <0,05). Keyword: Accelerated Learning Cycle, Mathematical Connection